Mapping the Distribution and Discharge of Plastic Pollution in the Ganga River - Sharma, Ekta; Ramachandran, Aishwarya; Dobriyal, Pariva; Badola, Srishti; Koldewey, Heather; Hussain, Syed Ainul; Badola, Ruchi (Sustainability, 2025)
The Ganga River, a lifeline for millions and a critical freshwater ecosystem, is under threat from escalating plastic pollution driven by widespread usage and inadequate disposal practices. While marine ecosystems have garnered extensive research attention, freshwater systems—particularly in the Global South—remain underexplored, leaving critical gaps in understanding plastic pollution’s sources and pathways. Addressing these gaps, the study documents the prevalence and typology of plastic debris in urban and underexplored rural communities along the Ganga River, India, aiming to suggest mechanisms for a reduction in source-based pollution. A stratified random sampling approach was used to select survey sites and plastic debris was quantified and categorised through transect surveys. A total of 37,730 debris items were retrieved, dominated by packaging debris (52.46%), fragments (23.38%), tobacco-related debris (5.03%), and disposables (single-use plastic cutleries) (4.73%) along the surveyed segments with varying abundance trends. Floodplains displayed litter densities nearly 28 times higher than river shorelines (6.95 items/m2 vs. 0.25 items/m2), with minor variations between high- and low-population-density areas (7.14 items/m vs. 6.7 items/m2). No significant difference was found between rural and urban areas (V = 41, p = 0.19), with mean densities of 0.87 items/m2 and 0.81 items/m2, respectively. Seasonal variations were insignificant (V = 13, p = 0.30), but treatment sites displayed significant variance (Chi2 = 10.667, p = 0.004) due to flood impacts. The findings underscore the urgent need for tailored waste management strategies integrating industrial reforms, decentralised governance, and community-driven efforts. Enhanced baseline information and coordinated multi-sectoral efforts, including Extended Producer Responsibility (EPR), are crucial for mitigating plastic pollution and protecting freshwater ecosystems, given rivers’ significant contribution to ocean pollution.